GROWTH AND YIELD RESPONSE OF SESAME (SESAMUM INDICUM L.) TO BITTER LEAF (VERNONIA AMYGDALINA DEL.) LEAF, STEM AND ROOT AQUEOUS EXTRACTS - Alege, Gbenga Olorunshola; Yakubu, Musa Ozigi; Egilla, Deborah Tini; Igata, David Franklin; Aliyu, Usman Ibrahim; Dauda, Danlami (FUDMA JOURNAL OF SCIENCES, 2022)
This study was carried out to assess the effect of leaf, stem and root aqueous extracts of Vernonia amygdalina on seed germination, growth and yield performance of Sesamum indicum. The aqueous extracts of the three plant parts were applied at concentrations of 25%, 50%, 75%, and 100% to sesame seeds in petri dish and compared with seeds treated with distilled water (control). The percentage of germinated seeds and lengths of radicle and plumule were measure within 10 days of sowing. The different concentrations of leaf, stem and root extracts of Vernonia amygdalina were applied to the seedlings of Sesamum indicum grown in pots and arranged in Complete Randomized Design (CRD). Data were obtained for number of germinated seeds, lengths of plumule and radicle while number of leaves, height of plant, stem girth, leaf length and leaf breadth were taken at 2,4, 6 and 8 Weeks After Planting (WAP). All data pooled were subjected to one way Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) is used to separate means. Significant reduction in germination percentage of sesame seeds was recorded in sesame grown with 100% concentration of aqueous stem extracts of Vernonia amygdalina (78.33%) which indicates inhibitory effect of the extract at the concentration. 25% aqueous root extracts of Vernonia amygdalina significantly stimulated early growth of the shoot (1.70cm) and root (1.60cm) in sesame seed. In this study, growth and yield of sesame were enhanced by 50% root extract of Vernonia amygdalina. This suggests that intermediate concentrations of
Keywords: Vernonia amygdalina, Sesamum indicum, Extracts, Germination, Yield